Water, sanitation and hygiene (WASH) and its association with stunting in developing countries in Asia: A systematic review - Rizaldi, Muhammad Addin; Ali, Khaidar; Rara, Swara Mega Hasanah; Panjaitan, Bintang Sri Rezeki (PT. Mega Science Indonesia, 2025)
Stunting is a vital health issue in developing Asian countries, where millions of individuals suffer from chronic malnutrition. Stunting not only is caused by chronic malnutrition but is also influenced by inadequate water supply, sanitation problems, and poor hygiene practices in the community. However, research on water, sanitation, and hygiene (WASH) and its association with stunting is limited, particularly in developing countries. This study aimed to analyze the associations between water, sanitation, and hygiene practices and the occurrence of stunting in Asia. This article is a systematic literature review using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A total of 1,002 articles were reviewed, of which 560 were published. Additionally, articles could be selected and dropped because they had no original research. After duplicate articles were removed, 168 articles were removed. The screening and extraction results revealed 14 articles eligible for review. After the article was reviewed and read, only five articles were eligible, and only 5 articles could be reviewed because the article discussed WASH and stunting in developing countries in Asia. Inadequate WASH practices were strongly associated with stunting among children under five years of age. An insufficient water supply and access to safe drinking water contribute to this condition, as inadequate water availability can increase the risk of stunting. Additionally, groundwater unfit for consumption increases the likelihood of undernutrition, including stunting, underweight, and wasting in children. Access to improved drinking water sources is essential for reducing stunting, as households with such access report lower stunting rates. Solutions to address stunting in children under five years of age include enhancing drinking water sources, improving sanitation facilities, and promoting better hygiene practices. Local governments should provide adequate water provision and accessible drinking water.